Carbon dots on LAPONITE® hybrid nanocomposites: solid-state emission and inter-aggregate energy transfer - Onishi, Bruno S. D. [UNESP]; Carneiro Neto, Albano N.; Bortoletto-Santos, Ricardo; Mastelaro, Valmor. R.; Carlos, Luis D.; Ferreira, Rute A. S.; Ribeiro, Sidney J. L. [UNESP] (Royal Soc Chemistry, 2024)
Correction for 'Carbon dots on LAPONITE (R) hybrid nanocomposites: solid-state emission and inter-aggregate energy transfer' by Bruno S. D. Onishi et al., Nanoscale, 2024, https://doi.org/10.1039/d3nr06336d.